Analysis of User Satisfaction Levels to Improve the Quality of Services in Nursing Education Laboratory: Analisis Tingkat Kepuasan Pengguna untuk Meningkatkan Kualitas Pelayanan Laboratorium Pendidikan Keperawatan - Hidayatul Ikhsan; Mery Lingga (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2024)
Purpose - The purpose of this research is to analyze user satisfaction levels, specifically those of lecturers and students, regarding the services provided by the Nursing Laboratory at the Padang Department of Nursing, Ministry of Health Polytechnic, Padang. Design/method/approach - This research employs a qualitative research approach with a descriptive quantitative method. It is an exploratory study that utilizes a questionnaire as the primary data collection instrument. The questionnaire is based on a Likert scale and encompasses five dimensions of satisfaction: Tangibles, Reliability, Responsiveness, Assurance, and Empathy Findings - The research results indicate gaps in respondent satisfaction frequencies in the dimensions of Responsiveness and Reliability, with scores of 86.7% and 87.6%, respectively. These scores are slightly lower compared to the other three dimensions: Tangibles (88.5%), Assurance (88.6%), and Empathy (88.4%). The overall average user satisfaction level is 87.9%, which falls within the 80.1%-100% interval, indicating a